The steroid-sparing effect of JAK inhibitors across multiple patient populations - Conigliaro, Paola; Minerba, Clara; Vendola, Andrea; Fiannacca, Luigi; Triggianese, Paola; Kroegler, Barbara; Greco, Elisabetta; Bergamini, Alberto; Chimenti, Maria Sole (Frontiers in Immunology, 2024)
JAK-inhibitors (JAK-i) represent an effective treatment in Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PsA). Oral glucocorticoids (OGC) are commonly used in combination with JAK-i to reach therapeutic target. We aimed to assess, in a real-life setting, the reduction of OGC dose during JAK-i treatment in active RA and PsA patients. We prospectively enrolled 103 patients (88 RA, 15 PsA) treated with JAK-i: 24% bio-naïve (b-naïve), 76% bDMARD-insufficient responders (bDMARD-IR) and 40% difficult to treat (D2T), defined as failure of ≥2 bDMARDs with different mechanism of action. Disease activity (DAS28 and DAPSA, VAS-pain, GH) and OGC dose was collected at baseline and after 3, 6 and 12 months (T3, T6, T12) of treatment. In all the cohort and in b-naïve patients we reported a reduction of OGC dose at all time-points; bDMARD-IR patients were able to reduce OGC dose at T3 and T12; D2T ones only at T3. We reported an improvement of disease activity and withdrawal of OGC as early as three months of therapy, at all time-points, regardless of line of bDMARD treatment. Chronic OGC may cause detrimental bone, metabolic, cardiovascular side effects and infections; therefore JAK-i steroid-sparing effect may be beneficial for patients in long-term treatment.